Heterogeneous phototransformation of halogenated polycyclic aromatic hydrocarbons: influencing factors, mechanisms and products - Y. Yang; Y. Yang; Y. Yang; Y. Liu; Y. Liu; Y. Liu; G. Zhu; B. Lin; S. Zhang; S. Zhang; S. Zhang; X. Li; et al. (Atmospheric Chemistry and Physics)
Chlorinated and brominated polycyclic aromatic hydrocarbons (XPAHs) are emerging pollutants widely found in atmospheric particulate matter (PM). However, their environmental transformation mechanisms remain poorly understood. In this study, we collected PM samples of varying sizes over a year for XPAH analysis and found that the average concentrations of XPAHs peaked in winter and were dominated by the contribution of PM1 (particulate matter ≤ 1 µm in aerodynamic diameter) (47.0 %). Correlation analysis with relevant meteorological parameters showed strong associations between XPAH fluctuations and PM, temperature and humidity. Hence, controlled laboratory experiments were conducted to explore the influence of particle size, sunlight duration, temperature, humidity and oxidant concentrations on XPAHs. Our results indicated that the transformation rates of XPAHs were influenced by the parent polycyclic aromatic hydrocarbon structures (with phenanthrene < fluoranthene < pyrene < benz[a]anthracene ≈ anthracene < benzo[a]pyrene) as well as the substitution of halogens (chlorinated < brominated). Furthermore, the photoirradiation promoted the heterogeneous transformation of XPAHs; this process was accelerated by the increased concentrations of reactive oxygen species and elevated temperature, peaking at a humidity level of 45 %. The transformation products were identified by nontarget analysis. According to that, we then proposed phototransformation pathways for XPAHs, suggesting a mechanism involving dehalogenation followed by oxidation. Predictions were made regarding the persistence, bioaccumulation, long-range transportation, and toxicities of XPAHs and their transformation products, showing a decrement in environmental risk as the transformation progressed. This study provides novel insights into the primary influencing factors for particulate XPAH variations and the mechanisms of heterogeneous phototransformation.